Potential Strategies to Improve the Quality of the Framework of Programmatic Assessment in Medical Education: Raising the Bar - Saurabh RamBihariLal Shrivastava; Rachmadya Nur Hidayah (Archives of Medicine and Health Sciences)
Assessment in medical education has a special role as it ascertains the acquisition of desired knowledge, skills, and learning outcomes expected from a medical graduate who will be a part of the health-care team. Programmatic assessment has gained wide attention, as it maximizes assessment for learning and also aids in the development of a strong assessment system, which enables teachers to take a data-driven decision about each student during the high-stakes assessment. In the case of programmatic assessment, the quality of the assessment is judged with the help of elements such as coherence, continuous, comprehensive, feasibility, purpose-driven, acceptability, and transparency. In conclusion, programmatic assessment has been linked with multiple benefits for the student, the teachers, and the administrators. However, to optimize the process of attainment of learning outcomes, it is the need of the hour that educators should take specific measures to augment the quality of all the elements of the assessment framework in programmatic assessment.